Balancing agricultural development and deforestation in the Brazilian Amazon - Cattaneo, Andrea (International Food Policy Research Institute, 2002)
Since the 1970s, federal policies promoting migration and encouraging agricultural development of large farms, logging, and ranching have led to the deforestation of vast areas of the Amazon rainforest.Though these policies have largely been replaced, deforestation continues. What effects do current macroeconomic and regional policies and events have on deforestation and on the well-being of settlers on the agricultural frontier? This report identifies the links between the agriculture and logging sectors in the Amazon, economic growth, poverty alleviation, and natural resource degradation in the region and in Brazil as a whole. It considers the effects of currency devaluation, building roads and other infrastructure in the Amazon, property rights, adoption of technological change, and fiscal incentives and disincentives to deforest.The results are sometimes counterintuitive, but shed new light on why slowing deforestation is so difficult and on the trade-offs between environmental and economic goals. -- Author's Abstract